Terapi Hipotermia Ringan Menurunkan Kadar Protein MMP-9 dan Memperbaiki FOUR Score pada Cedera Otak Traumatik Risiko Tinggi - ., Hendra; Wijaya, Halim; Prasetyo, Eko; Oley, Maximillian Ch. (Jurnal Biomedik : JBM, 2017)
Abstract: In this study, patients with high risk traumatic brain injury (TBI) were treated with mild therapeutic hypothermia and their serum MMP-9 levels as well as neurological outcome were evaluated. This was an experimental analytical study conducted at Intensive Care Unit Prof. Dr. R. D. Kandou Hospital, Manado. The results showed that there were 20 patients with high risk TBI (the FOUR score <7) prospective randomly assigned to mild therapeutic hypothermia and control groups. Patients were evaluated at the time of admission and after 72 hours. The serum MMP-9 level was examined by using enzyme-linked immunosorbent assay (ELISA) and the clinical outcome was evaluated by using the FOUR score. Levels of the variables were compared between the two groups. In the hypothermia group, level of serum MMP-9 was decreased (P > 0.05) after 72 hours and there was a significant improvement of the FOUR score (P < 0.05). Conclusion: Mild therapeutic hypothermia could reduce serum MMP-9 level and significantly improve the neurological outcome after 72 hours.Keyword: mild hypothermia, MMP-9, FOUR scoreAbstrak: Penelitian ini dilakukan terhadap penderita cedera otak akibat trauma (COT) risiko tinggi yang diberi perlakuan hipotermia ringan (HPTr) dengan mengevaluasi kadar MMP-9 serum dan hasil klinis yang dinilai melalui skor FOUR. Jenis penelitian ini ialah eksperimental analitik. Penelitian ini dilakukan di Intensive Care Unit (ICU) RSUP Prof. Dr. R. D. Kandou Manado. Terdapat total 20 pasien dengan COT risiko tinggi (skor FOUR <7) yang secara random dibagi dalam kelompok kontrol dan kelompok HPTr. Pasien dinilai saat masuk dan setelah 72 jam kemudian. Kadar MMP-9 serum dinilai menggunakan enzyme-linked immunosorbent assay (ELISA). Perbedaan level dari kedua variabel ini dibandingkan pada kedua kelompok. Hasil penelitian memperlihatkan bahwa pada kelompok perlakuan HPTr, kadar MMP-9 serum berkurang setelah 72 jam walaupun tidak bermakna (P > 0,05) dan terdapat peningkatan skor FOUR secara bermakna (P < 0,05). Simpulan: Perlakuan hipotermi ringan dapat menurunkan kadar MMP-9 serum dan memberikan peningkatan hasil klinis melalui penilaian skor FOUR setelah 72 jam kemudian.Kata kunci: hipotermi ringan, MMP-9, FOUR score